Enhancing endogenous capacity to repair a stroke-damaged brain: An evolving field for stroke research. (April 2018) - Zhao, Li-Ru; Willing, Alison
Highlights: Enhancing stroke recovery is highly important for stroke research. Lifelong brain plasticity makes its possible to be repaired years after stroke. Earlier intervention may not be an optimal time for brain repair. Neurovascular network rewiring is conclusively linked to stroke recovery. How to repair entire brain networks and function needs to be recognized in future. Abstract: Stroke represents a severe medical condition that causes stroke survivors to suffer from long-term and even lifelong disability. Over the past several decades, a vast majority of stroke research targets neuroprotection in the acute phase, while little work has been done to enhance stroke recovery at the later stage. Through reviewing current understanding of brain plasticity, stroke pathology, and emerging preclinical and clinical restorative approaches, this review aims to provide new insights to advance the research field for stroke recovery. Lifelong brain plasticity offers the long-lasting possibility to repair a stroke-damaged brain. Stroke impairs the structural and functional integrity of entire brain networks; the restorative approaches containing multi-components have great potential to maximize stroke recovery by rebuilding and normalizing the stroke-disrupted entire brain networks and brain functioning. The restorative window for stroke recovery is much longer than previously thought. The optimal time for brain repair appears to be at later stage of stroke rather than the earlier stage. It is expected that these new insights will advance our understanding of stroke recovery and assist in developing the next generation of restorative approaches for enhancing brain repair after stroke.